Students’ Attitudes toward Indonesian Language and Coaching Model Design based on Local Wisdom - Asep Hidayatullah; Vismaia Sabariah Damayanti; Yeti Mulyati; Andoyo Sastromiharjo (STAI Hubbulwathan Duri, 2023)
The objective of this study was to provide a description of students' attitudes towards the Indonesian language and to develop a model for promoting positive language attitudes. The participants in this study consisted of 30 students from FTTE Galuh University. The sample method employed in this study is a simple random sampling strategy. The investigation employed a descriptive analytical method. The required data for this study were obtained using a questionnaire technique and analysed through a series of processes including compilation, disassembly, reassembly, interpretation, and conclusion. As a result, language loyalty aspects get a score of 121 (80.67%), pride in language 112 (74.67%), and awareness of norms 114 (76%). Thus, it can be concluded that the majority of Galuh University FTTE students (77.33%) have a positive attitude towards Indonesian. The design of a coaching model to increase students' positive attitudes towards Indonesian was through practicum activities based on multiliteracy and Local wisdom.